Overview of Peak Expiratory Flow Rate in Elementary School Students in the Coastal Area of Hutumuri Village - Lutfhi, Muhammad; Tentua, Vebiyanti; Devi, Cokorda Istri Arintha (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Respiratory diseases are the most common cause of death in children, in this case most of them are obstructive disorders. Peak expiratory flow (PEF) is a tool for detecting airway obstruction, which the value is influenced by host and environmental factors. Examination of PEF aims to describe the condition of the large-calibre airway. A decrease in PEF values indicates an expiratory airways resistance. This study aimed to determine how the condition of pulmonary physiology in children living in the coastal area, with peak expiratory flow parameters in elementary school students in coastal areas, area of Hutumuri Village.Methods: The design used in this study was descriptive quantitative with cross-sectional method. This study took variables in the group of children aged 8-13 years, the group of children with weight between 15-36 kg, height of 118-139 cm, the group of children with a hobby of swimming, the group of children with a history of respiratory disease. The sampling technique used was total sampling with a total of 215 respondents in four elementary schools located in Hutumuri Village, South Leitimur District, Ambon City which included 53 Batu Gong Elementary School, Toisapu Elementary School, 52 Lawena Elementary School and Hutumuri Christian Elementary School.Results: The value of PEF rate increased in the group of children with aged ≥12-13 years, the group of children with body weight ≥36 kg, the group of children with height ≥139 cm, the group of children who did not have a history of respiratory disease, and the group of children with swimming as hobby.Conclusion: The average value of PEF in children who live in coastal areas had increased and of the 215 respondents studied, most were found in the normal PEF group or the percentage of 80-100% with 114 respondents (53.0%).